Student support and tuition fee systems in comparative perspective. Issue 11 (2nd November 2021) - Czarnecki, Krzysztof; Korpi, Tomas; Nelson, Kenneth
ABSTRACT: The purpose of this study is to outline a new approach to the comparative analysis of student finance systems based on social rights, an approach widely applied in other areas of social policy. It focuses on rights codified in national legislation and financed by central governments, and the collection of indicators measuring formal eligibility and entitlements using model family analyses techniques. We illustrate the usefulness of the approach by exploring the relationship between the generosity and the degree of low-income targeting of student support in 21 OECD countries. The results show that student support is less generous in countries that concentrate benefits on students from low-income families.